β1 Integrin-Mediated Adhesion Signalling Is Essential for Epidermal Progenitor Cell Expansion - Piwko-Czuchra, Aleksandra (Public Library of Science, 2009)
BACKGROUND: There is a major discrepancy between the in vitro and in vivo results regarding the role of β1 integrins in the maintenance of epidermal stem/progenitor cells. Studies of mice with skin-specific ablation of β1 integrins suggested that epidermis can form and be maintained in their absence, while in vitro data have shown a fundamental role for these adhesion receptors in stem/progenitor cell expansion and differentiation. METHODOLOGY/PRINCIPAL FINDINGS: To elucidate this discrepancy we generated hypomorphic mice expressing reduced β1 integrin levels on keratinocytes that developed similar, but less severe defects than mice with β1-deficient keratinocytes. Surprisingly we found that upon aging these abnormalities attenuated due to a rapid expansion of cells, which escaped or compensated for the down-regulation of β1 integrin expression. A similar phenomenon was observed in aged mice with a complete, skin-specific ablation of the β1 integrin gene, where cells that escaped Cre-mediated recombination repopulated the mutant skin in a very short time period. The expansion of β1 integrin expressing keratinocytes was even further accelerated in situations of increased keratinocyte proliferation such as wound healing. CONCLUSIONS/SIGNIFICANCE: These data demonstrate that expression of β1 integrins is critically important for the expansion of epidermal progenitor cells to maintain epidermal homeostasis.